The Effect of a Project-Based Learning Model on Learning Outcomes and Collaboration Skills - Mulyadi, Andi; Mustofa, Romy Faisal; Diella, Dea (Universitas Islam Negeri Walisongo Semarang, 2023)
This research was motivated by the lack of optimal learning outcomes and collaboration skills of students. The purpose of this study is to determine the effect of the project-based learning model on learning outcomes and student collaboration skills on ecosystem material. The research method used is Quasi Experiment with the matching-only posttest-only control group design. The study population is class X MIPA SMA Negeri 8 Tasikmalaya. Samples were taken using purposive sampling and obtained class X MIPA 1 as a control class and X MIPA 4 as an experimental class. The learning process in the control classroom uses the discovery learning model. Data collection techniques in the form of learning outcomes tests and non-tests using the Collaboration Self-Assessment Tool (CSAT) questionnaire. Data analysis using One Way Anova Test. The results of data analysis show that there is an influence of the project based learning model on students' learning outcomes and collaboration skills on ecosystem material in class X MIPA SMA Negeri 8 Tasikmalaya.